2017
DOI: 10.1177/1745499917740658
|View full text |Cite
|
Sign up to set email alerts
|

Two worlds of educational research? Comparing the levels, objects, disciplines, methodologies, and themes in educational research in the UK and Germany, 2005–2015

Abstract: Embedded in social worlds, education systems and research reflect distinct national trajectories. We compare two contrasting traditions of educational research (ER). Whereas British ER exhibits a multidisciplinary and pragmatic character, German ER reflects pedagogy and mainly humanities-based traditions. Yet, in both countries, policymakers’ growing demand for evidence in ER resulted in increased funding, specific research programs, and mandatory large-scale assessments. These have reshaped the field, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This resembles the trajectory of The Netherlands where PISA was largely ignored by the research community and contrasts with Sweden and Switzerland where international assessments had a major impact by strengthening their limited quantitative research traditions before participation (Gläser et al, ). Such a mediated impact of PISA contrasts starkly with Germany where the first PISA round in 2000 sparked widespread public outcry and political action, opening a window of opportunity for a new (empirical, quantitative and applied) methodological paradigm to emerge, also supported by public investments in capacity‐building and thematic funding programmes in educational research (Zapp & Powell, , ).…”
Section: Translating Global Trends Into Norwegian Educational Researcmentioning
confidence: 99%
See 2 more Smart Citations
“…This resembles the trajectory of The Netherlands where PISA was largely ignored by the research community and contrasts with Sweden and Switzerland where international assessments had a major impact by strengthening their limited quantitative research traditions before participation (Gläser et al, ). Such a mediated impact of PISA contrasts starkly with Germany where the first PISA round in 2000 sparked widespread public outcry and political action, opening a window of opportunity for a new (empirical, quantitative and applied) methodological paradigm to emerge, also supported by public investments in capacity‐building and thematic funding programmes in educational research (Zapp & Powell, , ).…”
Section: Translating Global Trends Into Norwegian Educational Researcmentioning
confidence: 99%
“…Taken together, projects focusing on equality, inclusion and welfare account for a fifth (19.6%) of all projects analysed, slightly below teaching and learning improvement (21.3%). This not only reflects strong and lasting values enshrined in Nordic policymaking, including education policy (Gundem, ; Lauglo, ; Karseth & Sivesind, ), but also contrasts strongly with other countries in which ideas of teaching and learning and societal impact (UK) and teaching and learning and professionalisation (Germany) were prioritised during the same period (Zapp, Marques, & Powell, ).…”
Section: Translating Global Trends Into Norwegian Educational Researcmentioning
confidence: 99%
See 1 more Smart Citation
“…Zapp et al (2017) make a similar point when they argue that research proposals to research councils (and the ESRC in particular) now include a separate section to estimate the potential impact of the work, with such funder requirements seen as shaping and driving ‘the research aims and the cognitive development of a discipline’ (p. 391). O’Connell (2019) found that the impact agenda is often perceived by education researchers as having negative effects, including the valuing of certain types of research, internal organisation rankings of departments based on impact, and the strengthening of a managerial culture within education.…”
Section: Main Themes Relevant To Understanding Formal and Informal St...mentioning
confidence: 99%